EXPLORING THE FUTURE OF QUANTUM COMPUTING: CHALLENGES AND OPPORTUNITIES IN COMPUTER ENGINEERING - Mohammed Nsaif Mustafa (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
We provide a high-level overview of the heterogeneous quantum computer architecture in this study since any future quantum computer will include both a classical and quantum computing component. The classical component is required for both error correction and the operation of algorithms that combine classical and quantum logic. We provide a thorough system stack that details all the levels involved in creating a quantum computer. The area of computer engineering may undergo a revolution as a result of the revolutionary paradigm that is quantum computing. This paper explores the potential of quantum computing and how it can affect Iraq computer engineering. Quantum technology's quick development brings opportunities and concerns that need to be thoroughly examined. The use of quantum computing in the field of computer engineering in Iraq faces a variety of difficulties. These include the dearth of qualified individuals with knowledge of quantum programming, the lack of widespread access to cutting-edge quantum gear, and the requirement for significant infrastructure improvements. The incorporation of quantum algorithms into current software frameworks also presents compatibility and optimization challenges. By establishing educational programmers, research projects, and strategic investments, academia, industry, and the government must work together to address these difficulties.